Optimasi Peran Dinas Pendidikan Kabupaten dalam Sistem Pengelolaan Bantuan Operasional Penyelenggaraan Pendidikan Anak Usia Dini - Sari, Puspita; Daryanto, Eka; Purba, Sukarman; Restu, Restu (Journal of Community Research and Service, 2024)
BOP PAUD management is part of education financing management. District education office has an important role in managing education funding, including BOP PAUD. The purpose of this qualitative research to provide information about the role of the district education office in the management of BOP PAUD, as well as to find challenges and obstacles as well as efforts made. It uses case study method. Data and information is collected by interview, participant observation and document study. The results inform that the role of the District Education Office in managing BOP PAUD is in the internal control system, outreach and education, monitoring and evaluation and validation of PAUD unit data. The challenges and obstacles are limited human resources, changes in the flow of information and digitalization that are very fast, weak coordination and lack of managerial capacity. Efforts are being made to overcome challenges and obstacles, by building a solid team, placing staff according to their competence, intelligent communication, and upholding discipline. Following up on the findings in this study, the District Education Office requires an internal agency and regional government policy to regulate the management of BOP PAUD. Also, increasing the human resource capacity of the District Education Office as an effort to improve excellent education services.